Planejamento como caminho para o desempenho superior de um Programa de Pós-graduação Stricto sensu - Martins Neto, João (2017)
In Brazil, the Graduate Programs stricto sensu are evaluated by the Coordination of Improvement of Higher Level Personnel - CAPES. Data from this institution show that in Brazil several stricto sensu Postgraduate Programs can improve their performance over the years, while others remain stagnant or close their activities. In order to understand this dynamic, this research describes and analyzes the actions and administrative routines that were consolidated in the planning and performance of the Postgraduate Program in Ecology and Conservation of Natural Resources (ECRN) of Federal University of Uberlândia (UFU), from the CAPES guidelines, starting from the evaluation proposal of implantation, occurred in 1999 until the year 2016. The Program was chosen for having improved its performance since its inception, being a reference for the survey of actions and administrative routines adopted by the course that may have contributed to this fact. Were sought theoretical input in planning theories and mainly in strategy theory as practice. The research is characterized as a case study with action research, in which data were collected from the direct observation of the researcher, documents of the Program, CAPES and UFU and unstructured interviews. For the analysis, quantitative and qualitative methods were used with the triangulation of the data, based on the analysis dimensions that followed the CAPES evaluation parameters: Program Proposal; Professors Group; Students Groups, Theses and Dissertations; Intellectual Production and Social Insertion. The results indicate that the ECRN started its activities in 1999 with the concept three (3) and, in 13 years of activity (1999 to 2012), by five triennial evaluations it obtained the concept six (6) in the last CAPES evaluation. It was possible to visualize an effective action of the human resources characterized by the adoption of behavior to objective actions towards a level of excellence and reference in the area of Biodiversity. In addition, it was observed the adoption of routine practices that led to the emergence of strategies for follow-up, adaptation, updating and achievement of goals. These findings are in line with strategy theory as practice. From the case studied, it was possible to create a technological product that was the creation of a checklist with the actions and administrative routines that were fundamental for the performance of the ECRN, according to the parameters of evaluation of CAPES. It is believed that from this checklist too many programs can adapt their actions and administrative routines to gradually improve their performance. As a limitation, the single case study does not allow the generalization of practices and administrative routines to other Programs and institutions. It is suggested for future work that the checklist be implemented in different programs of different areas of CAPES and that adaptations and improvements be suggested to this tool.